The Term ‘Lone Wolf’ and its Alternatives: patterns of Public and Academic Use from 2000 to 2020 - Berntzen, Lars Erik (Perspectives on terrorism, 2021)
Prominent cases of terror attacks planned and perpetrated by individuals have generated an ongoing public and academic debate about how to understand this phenomenon. The moniker "lone wolf" stands at the center of this debate. In this Research Note, we highlight three overarching points of criticism levelled at the use of this term: one conceptual, one normative and one empirical. While the solution to the latter problem primarily lies in being stringent, proposed solutions for the first two problems involved the exchange of the metaphor "lone wolf" with terms such as "lone actor" and "solo terrorist". This Research Note focuses on patterns in public, popular cultural and academic use of "lone wolf" as well as the proposed alternatives "lone actor" and "solo terrorist". It does so by utilizing data from Google Trends, Google Books Ngram Viewer and Google Scholar for the period 2000 to 2020. Trends in Google searches across the world indicate a moderate increase in public attention whereas using English language literature as a proxy for popular cultural attention shows a steady increase. Finally, academic use of the term "lone wolf" exploded in the aftermath of the July 22, 2011 terror attacks and has remained at high levels ever since. Among the proposed alternatives to "lone wolf", only "lone actor" has truly gained academic prominence. While overcoming some of the issues with the "lone wolf" metaphor, patterns in the data indicate that the neutrality and abstract nature of the term "lone actor" also comes with some drawbacks. To help counteract this, we suggest that researchers avoid using shorthand versions and consistently use the full term "lone actor terrorist".